Peranan Koperasi dalam Perekonomian Indonesia - Azhari Azhari (Universitas Serambi Mekkah, 2017)
This study aims to descriptively evaluate the existence and role of cooperatives in the Indonesian economy. This study uses a descriptive analysis. The number of cooperatives in Indonesia reached 21,135 units with a total membership of 15% of the total population of Indonesia. As many as 30% of cooperatives in Indonesia are inactive for various reasons. The percentage of cooperative contribution to Indonesia's gross domestic product is below 2%. Whereas employment, cooperatives are only able to absorb 0.5% of all Indonesian citizens who work. Some suggestions that can be made include; (1) Increase the participation of cooperative members; (2) Providing a conducive climate for cooperatives, access to financing and business development; (3) Improving counseling and training for managers, supervisors and apparatus of cooperative supervisors; and (4) Encouraging Micro, Small and Medium Enterprises (MSMEs) to establish secondary cooperatives.